2021
DOI: 10.1101/2021.06.02.446644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drivers of Transcriptional Variance in Human Intestinal Epithelial Organoids

Abstract: Background & Aims: Human intestinal epithelial organoids (enteroids and colonoids) are tissue cultures used for understanding the physiology of the intestinal epithelium. Here, we explored the effect on the transcriptome of common variations in culture methods, including extracellular matrix substrate, format, tissue segment, differentiation status, and patient heterogeneity. Methods: RNA-sequencing datasets from 251 experiments performed on 35 human enteroid and colonoid lines from 28 patients were aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 108 publications
(153 reference statements)
0
10
0
Order By: Relevance
“…showed that brain organoids had more than randomly expected variability (Quadrato et al, 2017; Velasco et al, 2019), though this variability was comparable to the one observed in vivo (Velasco et al, 2019). Other studies in epithelial intestinal organoids similarly showed a high degree of inter-organoid variability (Criss et al, 2021; Hof et al, 2021; Mohammadi et al, 2021). These findings suggest that there is significant, uncharacterised interorganoid heterogeneity across organoid systems, which is important to understand and subsequently model ahead of perturbation.…”
Section: Introductionmentioning
confidence: 70%
“…showed that brain organoids had more than randomly expected variability (Quadrato et al, 2017; Velasco et al, 2019), though this variability was comparable to the one observed in vivo (Velasco et al, 2019). Other studies in epithelial intestinal organoids similarly showed a high degree of inter-organoid variability (Criss et al, 2021; Hof et al, 2021; Mohammadi et al, 2021). These findings suggest that there is significant, uncharacterised interorganoid heterogeneity across organoid systems, which is important to understand and subsequently model ahead of perturbation.…”
Section: Introductionmentioning
confidence: 70%
“…Other recent important developments include the generation of apical-out (or reverse polarity) organoids which allows easier access to the apical membrane of the intestinal epithelium for exposure studies (120), and the ability to "inflame" organoids through treatment with a cocktail of inflammatory mediators (121). In addition, recently it has been demonstrated that as expected human ileal and colonic epithelial organoids express higher levels of the FXR and bile salt transporter genes in comparison to duodenal epithelial organoids (122). One of the major gaps in knowledge is how BA receptor activation can influence the aforementioned IBD-relevant downstream pathways such as autophagy and the inflammasome pathway in the human intestinal mucosa.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In contrast to C. difficile and S. enterica serovar Typhimurium, important multi-resistant pathogens such as extended-spectrum beta-lactamase-producing ExPEC (ESBL-ExPEC) and VRE reside in the gut microbiome and do not seem to inflict damage to the host, up until the moment of invasion and infection in other body sites (75)(76)(77). ESBL-ExPEC and VRE are important examples of opportunistic multidrug resistant pathogens where gut colonization precedes infections (76,78).…”
Section: The Role Of the Gut Microbiome In Colonization Resistancementioning
confidence: 99%
“…In contrast to C. difficile and S. enterica serovar Typhimurium, important multi-resistant pathogens such as extended-spectrum beta-lactamase-producing ExPEC (ESBL-ExPEC) and VRE reside in the gut microbiome and do not seem to inflict damage to the host, up until the moment of invasion and infection in other body sites (75)(76)(77). ESBL-ExPEC and VRE are important examples of opportunistic multidrug resistant pathogens where gut colonization precedes infections (76,78). Especially in hospitalized patients, that frequently receive antibiotics, initial colonization by these opportunistic pathogens may lead to intestinal overgrowth increasing the risk of causing infections and outbreaks (75,76,(78)(79)(80)(81)(82)(83)(84).…”
Section: The Role Of the Gut Microbiome In Colonization Resistancementioning
confidence: 99%
See 1 more Smart Citation